Mother's Knowledge Level About Clean and Healthy Life Behavior (PHBS) in Household Order - Asri Jumadewi; Irwana Wahab; Putro Simeulu; Yenni Sasmita (Nur Science Institute, 2022)
Predisposing, supporting and motivating factors are factors that can manifest the behavior of a person and society. A person's behavior will become a habit in activities and doing health. The Clean and Healthy Behavior Program (PHBS) is a health program to improve the health status of the community. PHBS has long been known, and echoed by the government, especially the ministry of health in household arrangements. PHBS in this order becomes the expected behavior in the family to encourage health behavior. The indicators for the success of PHBS can be seen from delivery that must be assisted by health workers, providing exclusive breastfeeding, weighing infants and toddlers regularly, washing hands with soap and clean water, using clean water, healthy latrines, eradicating mosquito larvae, consuming fruit and vegetables and doing physical activity every day, and coupled with the PHBS program for households not smoking in the house. This research was conducted in the village of Mata Ie Pasie Raja, South Aceh Regency for the purpose of knowing how the picture of family PHBS in the village of Mata Ie Pasie Raja is. Descriptive research method was conducted by conducting interviews using a questionnaire. Respondents who became the sample of this study were housewives totaling 55 people. The results showed that the level of knowledge of respondents was in the moderate category, as many as 26 (47.2%), the rest were in the good category were 17 people (30.9%) and in the less category as many as 12 people (21.8%). This knowledge can be increased by providing counseling and assistance to the family PHBS program by the government and the local health office, so that knowledge dissemination can increase and influence the community in general.